War remains: mediations of suffering and death in the era of the world wars - Cronqvist, Marie; Sturfelt, Lina (Kriterium, 2018)
Regarding the pain of mothers /Sofi Qvarnström --Visualizing war victims /Lina Sturfelt --A sensory experience /Kristin Skoog --A means to an end /A°sa Bergström --Journalism after mass death /Marie Cronqvist --Framing the waste of war /Sara Kärrholm --Circulating Nazi imagery /Laura Saarenmaa.